Sweden : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 1999)
This 1999 Article IV Consultation highlights that Sweden's real GDP growth accelerated to 2.9 percent in 1998, as a result of a strengthening of domestic demand. Private consumption was aided by sizable real wage increases, declining unemployment, increased government transfers to households, and rising asset prices, while investment was boosted by a combination of improved profit conditions, a healthy economic outlook, and lower interest rates. Employment rose by 1 1\2 percent in 1998, and by a further 2 percentage points during the first half of 1999.